JOINT PROPERTY OWNERSHIP OF SPOUSES ACCORDING TO SHARIAH TRADITIONS AND PRINCIPLES IN MALAY REGION - Nurafni; Aslati; Darmawan Tia Indrajaya (RADJA PUBLIKA, 2025)
This study examines the interaction between the concept of shared property in Malay custom and the principle of